Reenvisioning Welsh Postcompulsory Education - Hazelkorn, Ellen (International Higher Education, 2018)
In 2015, the Welsh government commissioned a review of its postcompulsory education system. Recommendations included the creation of a single regulatory, oversight, and coordinating authority bringing together further, higher, and adult learning. By its swift endorsement of the report’s principles and recommendations, the Welsh government conspicuously diverged from the market–demand driven approach adopted by the UK government for England.